1997
DOI: 10.1253/jcj.61.119
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in Cardiac Ischemia-Reperfusion Injury

Abstract: During cardiac surgery, ischemia-reperfusion injury (IRI) is thought to be a major factor in intraoperative myocardial damage. Coronary endothelial cells have been thought to play an important role in the pathogenesis of cardiac IRI. Release of nitric oxide (NO) from coronary endothelial cells is impaired following myocardial ischemia, and this may contribute to the vulnerability of the coronary circulation to thrombus-formation and vasospasm. Several experimental studies have found that NO has a cardioprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 56 publications
3
13
0
1
Order By: Relevance
“…These specific features were probably related to high activity of antioxidant systems in the organism that play a role in myocardial protection from reperfusion injury. Our hypothesis is confirmed by published data that NO activates expression of genes for antioxidant enzymes [11]. It cannot be excluded that the development of late reperfusion arrhythmias is associated with apoptosis in myocardial cells, which results from free radical generation under conditions of oxygen supply to damaged heart tissue [10,12].…”
Section: Resultssupporting
confidence: 84%
“…These specific features were probably related to high activity of antioxidant systems in the organism that play a role in myocardial protection from reperfusion injury. Our hypothesis is confirmed by published data that NO activates expression of genes for antioxidant enzymes [11]. It cannot be excluded that the development of late reperfusion arrhythmias is associated with apoptosis in myocardial cells, which results from free radical generation under conditions of oxygen supply to damaged heart tissue [10,12].…”
Section: Resultssupporting
confidence: 84%
“…Finally, our interest in assessing the peroxynitritequenching activity of herbal teas stems from the apparent involvement of peroxynitrite anions in the ethiogenesis of pathologies associated with ischemiareperfusion injury (Nonami, 1997), and in the oxidation of LDL (Carr et al, 2000), a key atherogenic event.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that L-Arg is a precursor of NO, which can increase coronary vasodilation, scavenge various free radicals, inactivate Fe-S centers of XO and suppress XO activity as well as inhibit platelet and neutrophil adhesion to the endothelium [33,34] . Hence, the protective role of NO is probably a result of its ability to scavenge free radicals, reduce lipid peroxidation, and inhibit XO, which are in accordance with our results for the E+Arg group.…”
Section: Discussionmentioning
confidence: 99%